ANALISIS IMPLEMENTASI KEBIJAKAN PEMBANGUNAN INSFRASTRUKTUR DI DESA DEWASARI KECAMATAN CIJEUNGJING KABUPATEN CIAMIS - Meita Imansari; Kiki Endah; Arie Budiawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine how the implementation of infrastructure development policies in Dewasari Village, Cijeungjing District, Ciamis Regency. Infrastructure plays an important role in supporting community activities and local economic growth. However, in its implementation, infrastructure development in Dewasari Village has not been running optimally. The problems identified include low community participation, limited budget, lack of supervision, and infrastructure quality that does not meet the Indonesian National Standard (SNI). This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. Informants in this study consisted of village heads, village officials, community leaders, and local residents. The results of the study indicate that the implementation of infrastructure development policies in Dewasari Village still faces various obstacles, both in terms of technical, managerial, and social aspects. Therefore, it is necessary to increase the capacity of village officials, budget transparency, and active community involvement to achieve more effective and sustainable development results.